A new species of Metadorcinus Kriesche from Brazil with notes on the genus (Coleoptera: Scarabaeoidea: Lucanidae) - Grossi, Paschoal C.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2007)
Metadorcinus ranki n. sp. (Lucanidae: Lucaninae: Sclerostomini) is described from Santa Catarina State, Brazil. The new species is easily distinguished from its congeners by the shape of the mandibles and canthi of males, and by the pronotal and elytral sculpture of both sexes. The synonymy of Beneshius under Metadorcinus is confirmed. Metadorcinus ditomoides is considered a valid species, not subspecies or synonym of B. cruentus. A key to the 14 species of Metadorcinus (including species previously included in Beneshius) and a checklist of the species are provided.Metadorcinus ranki sp. nov. (Lucanidae: Lucaninae: Sclerostomini) é descrita do Estado de Santa Catarina, Brasil. Esta nova espécie se diferencia das outras do gênero pela forma das mandíbulas e do cantus ocular dos machos, e pronoto e élitros de machos e fêmeas. A sinonímia de Beneshius com Metadorcinus é confirmada. Metadorcinus ditomoides se considera como espécie válida, e não subespécie ou sinônimo de M. cruentus. Também se apresentam uma chave para identificação das 14 espécies de Metadorcinus (incluindo as espécies previamente incluídas em Beneshius) e uma lista das espécies do gênero.Se describe a Metadorcinus ranki sp. nov. (Lucanidae: Lucaninae: Sclerostomini) del Estado de Santa Catarina, Brasil. La nueva especie se distingue de las demás por la forma de las mandíbulas y canto ocular de los machos, y pronoto y élitros de machos y hembras. Se confirma la sinonimización de Beneshius con Metadorcinus. Se considera a Metadorcinus ditomoides como especie válida, y no subespecie o sinónimo de M. cruentus. Se presenta además una clave para identificación de las 14 especies de Metadorcinus (incluyendo a las especies incluidas anteriormente en Beneshius) y un listado de las especies del género.